2019
DOI: 10.1111/jph.12852
|View full text |Cite
|
Sign up to set email alerts
|

Amaranthus caudatus subsp. mantegazzianus: A new host of ‘Candidatus Phytoplasma hispanicum’ (subgroup 16Sr XIII‐A)

Abstract: In Argentina, amaranth is a promising crop due to high nutritional quality and ability to grow in a diversity of environments. In areas cultivated with amaranth, were observed plants exhibiting slow growth, deformed leaves, proliferation of shoots and malformed lateral panicles. Field survey revealed up to 96% disease incidence and 92% of the seeds collected from mother plants produced diseased seedlings. A phytoplasma was detected in association with seedlings and adult plants using nested PCR assays. Molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Xanthomonas differs from non-pathogenic bacteria in that it relies on a variety of potent substances secreted through different kinds of protein secretion systems, predominantly the type III secretion system, to suppress host immunity and to obtain nutrients from plants. Amaranth was considered a promising crop in Argentina ( Noelting et al, 2019 ), but was found to be a host of Xanthomonas euvesicatoria ( Santos et al, 2020 ), Curtobacterium flaccumfaciens pv. flaccumfaciens ( Nascimento et al, 2020 ), and Xanthomonas citri subsp.…”
Section: Resultsmentioning
confidence: 99%
“…Xanthomonas differs from non-pathogenic bacteria in that it relies on a variety of potent substances secreted through different kinds of protein secretion systems, predominantly the type III secretion system, to suppress host immunity and to obtain nutrients from plants. Amaranth was considered a promising crop in Argentina ( Noelting et al, 2019 ), but was found to be a host of Xanthomonas euvesicatoria ( Santos et al, 2020 ), Curtobacterium flaccumfaciens pv. flaccumfaciens ( Nascimento et al, 2020 ), and Xanthomonas citri subsp.…”
Section: Resultsmentioning
confidence: 99%
“…mantegazzianus and A. retroflexus , were reported as hosts of ‘ Ca . P. hispanicum’ (subgroup 16Sr XIII‐A) from Argentina (Noelting et al. , 2019) and ‘ Ca .…”
Section: Figurementioning
confidence: 99%
“…mantegazzianus and A. retroflexus, were reported as hosts of 'Ca. P. hispanicum' (subgroup 16Sr XIII-A) from Argentina (Noelting et al, 2019) and 'Ca. Phytoplasma ziziphi' (subgroup 16SrV-B) in China (Long et al, 2011), respectively.…”
mentioning
confidence: 99%